Extracting Firm Information from Administrative Records: The ASSD Firm Panel - Martina Fink; Esther Segalla; Andrea Weber; Christine Zulehner (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
This paper demonstrates how firm information can be extracted from administrative social security records. We use the Austrian Social Security Database (ASSD) and derive firms from employer identifiers in the universe of private sector workers. To correctly pin down entry end exits we use a worker flow approach which follows clusters of workers as they move across administrative entities. This procedure enables us to define different types of entry and exit such as start-ups, spinoffs, closures, or take-overs. We show that our firm definition results in a demography which is comparable to official statistics of firm registers. The resulting database, covering the period of 1976 to 2006, is a valuable resource for future research on industry evolution in Austria.
Keywords: 330; administrative data; definition of firms; entry and exit types; worker flows